2016
DOI: 10.1128/mcb.00744-15
|View full text |Cite
|
Sign up to set email alerts
|

Fas-Associated Factor 1 Negatively Regulates the Antiviral Immune Response by Inhibiting Translocation of Interferon Regulatory Factor 3 to the Nucleus

Abstract: This study is designed to examine the cellular functions of human Fas-associated factor 1 (FAF1) containing multiple ubiquitin-related domains. Microarray analyses revealed that interferon-stimulated genes related to the antiviral response are significantly increased in FAF1-knockdown HeLa cells. Silencing FAF1 enhanced the poly(I·C)- and respiratory syncytial virus (RSV)-induced production of type I interferons (IFNs), the target genes of interferon regulator factor 3 (IRF3). IRF3 is a key transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Pathway enrichment analysis of YTHDF2 in LGG by GESA found that the genes correlated with YTHDF2 were more significantly enriched in cell cycle, TCA cycle, DNA replication, and the FAS signaling pathway. Interestingly, the most significant gene positively associated with YTHDF2, FAF1, can regulate antiviral immunity ([ 80 , 81 ]). Moreover, notch family genes (the pathway found in the enrichment analysis) were prognostic biomarkers and correlated with immune infiltrates in gastric cancer ([ 82 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis of YTHDF2 in LGG by GESA found that the genes correlated with YTHDF2 were more significantly enriched in cell cycle, TCA cycle, DNA replication, and the FAS signaling pathway. Interestingly, the most significant gene positively associated with YTHDF2, FAF1, can regulate antiviral immunity ([ 80 , 81 ]). Moreover, notch family genes (the pathway found in the enrichment analysis) were prognostic biomarkers and correlated with immune infiltrates in gastric cancer ([ 82 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible that PLK2 catalyzes the phosphorylation of the substrate responsible for IRF3 nuclear trafficking. IRF3 translocation was shown to be mediated by PTEN, Rubicon, and IPO5/ Importin-b3 (13,14,33), which may be regulated by PLK2.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of characterized inhibitors of IRF3 activity target IRF3 for ubiquitination and degradation, for example Forkhead box protein O1 (FOXO1) (19), RTA-associated ubiquitin ligase (RAUL) (20), and tripartite motif-containing 26 (TRIM26) (21). Fas-associated factor 1 has been shown to prevent interactions of IRF3 with importins (22), thus inhibiting nuclear trafficking in response to viral stimuli. An additional inhibitor of IRF3, cellular FLICE-like inhibitory protein (cFLIP L ) inhibits IFN-␤ transcription by binding to IRF3 and preventing its association with CBP within the nucleus (23).…”
mentioning
confidence: 99%